Stress ulcer prophylaxis in adult intensive care unit patients – a protocol for a systematic review. Issue 6 (25th March 2018) - Barbateskovic, M.; Marker, S.; Jakobsen, J. C.; Krag, M.; Granholm, A.; Anthon, C. T.; Perner, A.; Wetterslev, J.; Møller, M. H.
Abstract : Background: In the intensive care unit (ICU), stress ulcer prophylaxis with proton pump inhibitors or histamine‐2‐receptor antagonists is standard of care although gastrointestinal bleeding remains uncommon. It remains unknown whether its use is associated with benefits or harms and the quality of evidence supporting the use of stress ulcer prophylaxis has been questioned. Accordingly, the objective of this systematic review was to critically assess the evidence from randomized clinical trials on the benefits and harms of stress ulcer prophylaxis vs. placebo or no prophylaxis in adult ICU patients. Methods: We will systematically search for randomized clinical trials in major international databases. Two authors will independently screen and select trials for inclusion, extract data and assess the methodological quality using the Cochrane risk of bias tool. Any disagreement will be resolved by consensus. We will perform conventional meta‐analyses using Review Manager, and STATA 15, and we will assess the risk of random errors using Trial Sequential Analysis. Also, we will assess and report the overall quality of evidence for all outcomes according to GRADE. Discussion: The evidence on the benefits and harms of stress ulcer prophylaxis in adult ICU patients is unclear and an updated systematic review is warranted as new trials have been published. To control risks of systematic and random errors, we will use Cochrane and GRADE methodology and Trial Sequential Analysis. Our ambition with this systematic review is to provide updated, reliable and precise data to better inform decision makers on the use of stress ulcer prophylaxis in adult ICU patients.